« Vous pouvez entendre les mâchoires de l’arme de l’ange ». Le traducteur humain face à la traduction automatique dans le contexte littéraire : Les Livres de Jakób d’Olga Tokarczuk - Mitura, Magdalena (Studia Romanica Posnaniensia, 2024)
The dynamic development of automatic translators raises questions about the future of human translators. The aim of this article is to evaluate the French versions of an excerpt from The Books of Jacob by Olga Tokarczuk, made by Systran, Google Translate and DeepL, and to compare them with the reference translation made by a human translator. The translations were carried out in 2019 as part of the ATLAS association project ‘L’Observatoire de la traduction automatique’. The analyses show that the inability to interpret the original in a complex way leads to weaknesses in machine translators. This proves that the position of the human translator remains unthreatened in the field of translating high-quality literary texts.